Disagreements. - Cohnitz, Daniel; Marques, Teresa (Erkenntnis)
This special issue of Erkenntnis is devoted to the varieties of disagreement that arise in different areas of discourse, and the consequences we should draw from these disagreements, either concerning the subject matter and its objectivity, or concerning our own views about this subject matter if we learn, for example, that an epistemic peer disagrees with our view. In this introduction we sketch the background to the recent philosophical discussions of these questions, and the location occupied therein by the articles in this collection.